Towards minimal empirical uncertainty bounds of damping estimates of an offshore wind turbine in idling conditions. (15th May 2023) - Kjeld, Jonas Gad; Avendaño-Valencia, Luis David; Brandt, Anders; Christensen, Silas Sverre; Andersen, Jacob Karottki Falk
Abstract: Structural damping is a critical quantity for condition assessment and fatigue lifetime prediction in wind energy. Its estimation from operational vibration data comes with a considerable amount of uncertainty, derived from environmental and operational variability and from the quality of the estimation process itself. In this paper, we aim to determine experimentally the damping values and their least possible uncertainty bounds for the first two modes of an idling offshore wind turbine. For this purpose, we use field measurements from a 3.6 MW offshore wind turbine located at the DanTysk wind farm. We select a subset of cases from the wind turbine on idling conditions for a confined interval of environmental and operational conditions, in an attempt to minimize operational variability in the damping estimates. In addition, we make a study on the adjustment parameters of the automated operational modal analysis method, aiming at obtaining the most consistent damping estimates. As a result of the proposed methodology, it is possible to confine the 90% confidence intervals of the damping ratio estimates of the first two tower modes within 0.8 and 1.1 percentual points in the fore-aft and the side-to-side direction, respectively. Highlights: We investigate long-term vibration monitoring data from an offshore wind turbine. We seek to minimize the estimation uncertainty of modal parameter estimates. To that end, we investigate the effect of the adjustment parameters of Automated OMA. In parallel, we use data from a confined interval of operational conditions. Uncertainty bounds of damping estimates of the first two OWT modes are determined.